2018
DOI: 10.1177/1120672118795399
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine expression in tears of patients with glaucoma or dry eye disease: A prospective, observational cohort study

Abstract: Different cytokine/chemokine expression profiles in tears of patients with primary open-angle glaucoma and dry eye disease strongly suggest the involvement of a variety of signaling pathways in the pathogenesis of these ophthalmic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 37 publications
7
30
0
Order By: Relevance
“…Thus, it was found that the ratio of ω-6 (AA) to ω-3 (DHA + EPA) fatty acids is increased in DES patients [21], which concurs with our observations (see Figure 3). Furthermore, a number of works reported DES-associated growth of the TF level of PGE2, which is recognized as a hallmark of the disease [21][22][23]44]. Consistently, in our experiments, PGE2 exhibited the most pronounced elevation among the identified mediators (see Figure 3).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, it was found that the ratio of ω-6 (AA) to ω-3 (DHA + EPA) fatty acids is increased in DES patients [21], which concurs with our observations (see Figure 3). Furthermore, a number of works reported DES-associated growth of the TF level of PGE2, which is recognized as a hallmark of the disease [21][22][23]44]. Consistently, in our experiments, PGE2 exhibited the most pronounced elevation among the identified mediators (see Figure 3).…”
Section: Discussionsupporting
confidence: 90%
“…IL-12 inhibits apoptosis of ganglion cells and then protects the optic nerve. IL-4 plays an important role during the process of optic nerve injury, and its high expression represents serious optic nerve injury (21,22). These studies are consistent with our conclusions.…”
Section: Lncrna Malat1 Lncrna Anril ---------------------------------supporting
confidence: 92%
“…Moreover, the proinflammatory IL-1β is a key protein that acts as the main potent mediator of ocular diseases, inducing tissue damage [27]. A recent study conducted by Tsai and colleagues evaluated the levels of vitreous cytokines in patients with diabetic retinopathy [2].…”
Section: Discussionmentioning
confidence: 99%